D-Arg0-Bradykinin-Arg-Arg, a Latent Vasoactive Bradykinin B2 Receptor Agonist Metabolically Activated by Carboxypeptidases - Bachelard, Hélène; Charest-Morin, Xavier; Marceau, François (Frontiers in Pharmacology, 2018)
We previously reported hypotensive and vasodilator effects from C-terminally extended bradykinin (BK) sequences that behave as B2 receptor (B2R) agonists activated by vascular or plasma peptidases. D-Arg0-BK-Arg-Arg (r-BK-RR) is a novel prodrug peptide hypothetically activated by two catalytic cycles of Arg-carboxypeptidases (CPs) to release the direct agonist D-Arg0-BK. N-terminally extending the BK sequence with D-Arg0 in the latter peptide was meant to block the second kinin inactivation pathway in importance, aminopeptidase P. The affinity of r-BK and r-BK-RR for recombinant B2R was assessed using a [3H]BK binding displacement assay. Their pharmacology was evaluated in human isolated umbilical vein, a contractile bioassay for the B2R, in a morphological assay involving the endocytosis of B2R-green fusion protein (GFP) and in anesthetized rats instrumented to record hemodynamic responses to bolus intravenous injection of both peptides. r-BK exhibited an affinity equal to that of BK for the rat B2R, while r-BK-RR was 61-fold less potent. In the vein and the B2R-GFP internalization assay, r-BK was a direct agonist unaffected by the blockade of angiotensin converting enzyme (ACE) with enalaprilat, or Arg-CPs with Plummer’s inhibitor. However, the in vitro effects of r-BK-RR were reduced by these inhibitors, more so by enalaprilat. In anesthetized rats, r-BK and r-BK-RR were equipotent hypotensive agents and their effects were inhibited by icatibant (a B2R antagonist). The hypotensive effects of r-BK were potentiated by enalaprilat, but not influenced by the Arg-CPs inhibitor, which is consistent with a minor role of Arg-CPs in the metabolism of r-BK. However, in rats pretreated with both enalaprilat and Plummer's inhibitor, the hypotensive responses and the duration of the hypotensive episode to r-BK were significantly potentiated. The hypotensive responses to r-BK-RR were not affected by enalaprilat, but were reduced by pre-treatment with the Arg-CPs inhibitor alone or combined with enalaprilat. Therefore, in vivo, Arg-CPs activity is dominant over ACE to regenerate the B2R agonist r-BK from r-BK-RR, a prodrug activator of the B2R. A B2R agonist activated only at the level of the microcirculation by resident peptidases could be developed as an intravenously infused drug for ischemic diseases.